2014
DOI: 10.1159/000357350
|View full text |Cite
|
Sign up to set email alerts
|

A New Clinical Scoring System to Define Pneumonia following Esophagectomy for Cancer

Abstract: Background: Pneumonia is a frequently observed complication following esophagectomy. The lack of a uniform definition of pneumonia leads to large variations of pneumonia rates in literature. This study was designed to develop a scoring system for diagnosing pneumonia following esophagectomy at the hospital ward. Methods: In a prospective cohort study of esophagectomy patients, known risk factors for pneumonia, temperature, leukocyte count, pulmonary radiography and sputum culture added were evaluated. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…9 Very few data are available on the effect on systematic inflammatory response to surgical trauma in case of HMIE. 15,16 Moreover, WBC resulted to be associated with anastomotic leak after esophagectomy in multivariate logistic regression with albumin and CRP. Maas et al 11 reported a peak of inflammatory activity after esophagectomy on day 1 as shown by IL8 serum level, thus, we considered CRP serum levels on day 1 as primary outcome.…”
Section: Discussionmentioning
confidence: 93%
“…9 Very few data are available on the effect on systematic inflammatory response to surgical trauma in case of HMIE. 15,16 Moreover, WBC resulted to be associated with anastomotic leak after esophagectomy in multivariate logistic regression with albumin and CRP. Maas et al 11 reported a peak of inflammatory activity after esophagectomy on day 1 as shown by IL8 serum level, thus, we considered CRP serum levels on day 1 as primary outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Although postoperative recovery has improved owing to the introduction of minimally invasive techniques, centralization of surgery and enhanced recovery programmes, the postoperative complication rate remains high. The most common complication after oesophagectomy is pneumonia. Depending on the definition, up to 40 per cent of patients develop this complication.…”
Section: Introductionmentioning
confidence: 99%
“…The CDC is a valuable tool that enables objective and detailed documentation, as well as defined grades of the severity of postoperative complications [10] . The UPSS was designed as a new clinical scoring system to define pneumonia following esophagectomy for cancer by van der Sluis et al [11] . The UPSS is estimated using temperature, the leukocyte count and pulmonary radiography findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy of PR is unclear for patients with esophageal cancer who undergo esophagectomy. Therefore, the aim of this study was to clarify the efficacy of PR for reducing respiratory complications after esophagectomy as evaluated through the use of the Clavien-Dindo classification (CDC) [10] and the Utrecht Pneumonia Scoring System (UPSS) [11] .…”
Section: Randomized Controlled Study To Evaluate the Efficacy Of A Prmentioning
confidence: 99%
See 1 more Smart Citation